Synthesis of 3-(Chlorosulfonylaryl) Phthalides and Their Reactions with Amino Pyridines - Al-Hamdany, R.; Fataftah, Z.; Abu-Durrah, B. (Asian Journal of Chemistry, 2010)
Certain new sulfonamido derivatives having heterocyclic moiety (2a-band 3a-e) have been synthesised by the reaction of 3-(chlorosulfonatedaryl) phthalides (If-j) with aminopyridines in the presence of dry pyridine.The chlorosulfonated aryl phthalides were synthesised from the corresponding3-arylphthalides (1a-e). The structures of the isolated productswere confirmed from their spectral and elemental analyses data..